Emodin alleviates bleomycin-induced pulmonary fibrosis in rats. (16th November 2016) - Guan, Ruijuan; Zhao, Xiaomei; Wang, Xia; Song, Nana; Guo, Yuhong; Yan, Xianxia; Jiang, Liping; Cheng, Wenjing; Shen, Linlin
Highlights: Emodin improves pulmonary function in BLM-treated rats. Emodin inhibits BLM-induced expression of profibrotic molecules, including TNF-α, IL-6, TGF-β1, α-SMA and HSP-47 in the lungs. Emodin attenuates TGF-β1-induced myofibroblast differentiation and ECM deposition in human embryo lung fibroblasts. Emodin suppresses TGF-β1-activated Smad2/3 signaling pathway. Emodin suppresses TGF-β1-induced STAT3 phosphorylation. Abstract: Idiopathic pulmonary fibrosis (IPF) is a lethal lung disease with few treatment options and poor prognosis. Emodin, extracted from Chinese rhubarb, was found to be able to alleviate bleomycin (BLM)-induced pulmonary fibrosis, yet the underlying mechanism remains largely unknown. This study aimed to further investigate the effects of emodin on the inflammation and fibrosis of BLM-induced pulmonary fibrosis and the mechanism involved in rats. Our results showed that emodin improved pulmonary function, reduced weight loss and prevented death in BLM-treated rats. Emodin significantly relieved lung edema and fibrotic changes, decreased collagen deposition, and suppressed the infiltration of myofibroblasts [characterized by expression of α-smooth muscle actin (α-SMA)] and inflammatory cells (mainly macrophages and lymphocytes). Moreover, emodin reduced levels of TNF-α, IL-6, TGF-β1 and heat shock protein (HSP)-47 in the lungs of BLM-treated rats. In vitro, emodin profoundly inhibited TGF-β1-induced α-SMA, collagen IV and fibronectin expression in human embryo lung fibroblasts (HELFs). Emodin also inhibited TGF-β1-induced Smad2/3 and STAT3 activation, indicating that Smad2/3 and STAT3 inactivation mediates emodin-induced effects on TGF-β1-induced myofibroblast differentiation. These results suggest that emodin can exert its anti-fibrotic effect via suppression of TGF-β1 signaling and subsequently inhibition of inflammation, HSP-47 expression, myofibroblast differentiation and extracellular matrix (ECM) deposition.